Reflections on the Interpretation of the Locus of Control Concept in Social Research - De Grande, Pablo (Pensando Psicología, 2014)
This article proposes a revision of the locus of control concept as a useful tool within the field of research into perception of control and its effects on actions. Locus of control measures have been widely used within and outside psychology to link beliefs with individual actions, and they have proved useful in areas as diverse as education, health, labor mobility and cultural consumption. However, its success at the empirical level has led in some cases —according to its creator, Julian Rotter— to conceptual inaccuracies with respect to its definition and the interpretation of results. Is locus of control the same as a measure of self-efficacy? Should internal focus of control be seen as something positive and external locus of control as something negative? Is it possible to predict individual behavior using a generalized measure of locus of control? This paper contextualizes the locus of control measure in the theoretical space where it originated (social learning theory), and highlights some relevant interpretive points for its analysis and use.
Keywords: self-concept; wellbeing; externality; locus of control